Influences of formulation and process variables on the color parameters of Philippine orange (Dalandan) juice - De Guzman, Fiona Paula Ruiz; Gabriel, Alonzo A. (2007.)
ABSTRACT The influence of formulation variables, dilution and soluble solids content, and process conditions, heating time and temperature, on the color parameters, L*, a* and b*, of pasteurized dalandan juice (DJ) were studied. A rotatable Central Composite Design (CCD) was adapted in the preparation and pasteurization of the DJs. The CIE L*, a* and b* color parameters were measured using the HunterLab ColorFlex® Spectrophotometer. Predictive models were developed and analyzed. Dilution and heating time significantly reduced all color parameters. Soluble solids content significantly increased the L* and a* values but did not significantly affect the b* value, while temperature only affected the a* value by decreasing it and did not significantly affect the other color parameters.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Orange juice -- Philippines; Color in food; Citrus juices